Dear colleagues and readers of our journal (Condensed Matter Physics, 2014)
Dear colleagues and readers of our journal, Our journal has just turned 20 and we should like to thank all of you — our contributors, readers and colleagues in science for your invaluable help during this period. Started as a small scale regional scientific edition, we are happy to report essential growth of our journal in many aspects. The network of our contributors extended to representatives of 60 countries with the fraction of foreign authors increased from 25% in 1993–1997 to 65% in 2008–2013 years. Now, already for some years, our journal is covered in Thomson ISI Master journal list, is assigned the ISI impact factor and has become a member of CrossRef association of publishers.